Comparative Bioactivity of Bamboo Leaf Ash and Bularafa Diatomaceous Earth against Maize Weevil (Sitophilus zeamais Motschulsky) - M. K. Abdulbaki; E. Nwebor; D. Uzu; O. M. Arohunmolase; D. S. Daramola; D. E. Nwokpoku; F. O. Onyegbule; S. I. Nwaubani (Journal of Applied Sciences and Environmental Management, 2022)
Maize is one of the major staple foods in Sub-Saharan Africa and there is serious loss in maize storage due to insect damage. This study compared the bioactivity of Bamboo Leaf Ash (BLA) and Bularafa Diatomaceous Earth (BDE) against Maize Weevil (Sitophilus zeamais Motschulsky) under laboratory conditions. Insecto®, a commercialized DE was also tested as standard check. Adults of the insects were exposed on maize admixed with the BLA at dose rate of 5,000, 10,000 and 20,000ppm; BDE and insecto® at a dose rate of 1,000ppm, at 28.20C and 82.2% relative humidity. Mortality increased with increasing exposure duration and all treatments showed mortality of more than 80% after 14days post-treatment compared to negative control with 0%.The treatments suppressed F1 progeny. Treated grains have weight loss less than 4%, kennel damage less than 14% and grain germination showed no significant change. The decreasing efficacy of the dusts against this insect is Insecto®> BLA > BDE. BLA and BDE have potential for the management of insect pests of stored grain in Nigeria.